2021
DOI: 10.7189/jogh.11.05006
|View full text |Cite
|
Sign up to set email alerts
|

Sudden death of COVID-19 patients in Wuhan, China: A retrospective cohort study

Abstract: Background In December 2019, coronavirus disease 2019 (COVID-19) emerged in Wuhan city and rapidly spread throughout China. So far, it has caused ~ 4000 deaths in this country. We aimed to systematically characterize clinical features and determine risk factors of sudden death for COVID-19 patients. Methods Deceased patients with COVID-19 in Tongji hospital from January 22 to March 23, 2020 were extracted. Patients who died within 24 hours after admission were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Article of Shao reported that the prevalence of SCD was 1.8% in the population with COVID-19 (28). Also, according to Yang et al there was a higher SCD prevalence (10%) in the deceased population with COVID-19 (31).…”
Section: The Prevalence Of Ventricular Arrhythmia and Scd In Patients With Covid-19mentioning
confidence: 95%
See 2 more Smart Citations
“…Article of Shao reported that the prevalence of SCD was 1.8% in the population with COVID-19 (28). Also, according to Yang et al there was a higher SCD prevalence (10%) in the deceased population with COVID-19 (31).…”
Section: The Prevalence Of Ventricular Arrhythmia and Scd In Patients With Covid-19mentioning
confidence: 95%
“…Twenty-one studies , which included 13,790 hospitalized patients with COVID-19 with a mean age ranging from 50 to 70.3 years, and with sample sizes ranging from 54 to 4,526, were published from 2020 to 2021 [eight of them published in 2021 (11,15,16,19,(24)(25)(26)31), others in 2020 (12-14, 17, 18, 20-23, 27-30)]. Nine reports were from Asia [eight from China (13,16,18,21,22,28,29,31), one from Iran (19)], seven from USA (11,12,14,15,17,25,30), and five from Europe [three from Italy (20,24,27), one from Netherland (23), one from Germany (26)]. Besides, 15 of them were retrospective studies (11, 13, 15-19, 21-23, 27-31), 5 were prospective studies (12,14,20,25,26), and 1 was cross-section study (24).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…There is much to be done as thenatural history of this disease has yet to be elucidated and whilst there has been an emphasis on pulmonary findings, there are now increasing reports that Covid-19 may also affect the cardiovascular and other organ systems ( Babapoor-Farrokhran et al, 2020 ; Barton et al, 2020 ). In fact, Yang et al reported death of a small number of patients who died within a short period of time after admission, in other words, sudden death ( Yang et al, 2021 ). Moreover, sudden cardiac arrest and death had been reported as early as 2020 despite improvement of general condition and constitutional symptoms ( Shirazi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil recruitment is highly correlated with the severity of COVID-19. Higher neutrophil counts were observed in critically versus noncritically ill patients and in those who died suddenly after admission versus those who did not ( 61 , 62 ). These observations are consistent with our findings supporting enhanced neutrophil recruitment with the rapid development of lung pathology in beta variant-infected mice.…”
Section: Discussionmentioning
confidence: 96%